Healer or village leader's staff - Unidentified artist (Colorado State University. Libraries, 1901)
Detail of the head of the Healer or Village Leader's staff.
This item was part of an exhibition at the Avenir Museum of Design and Merchandising titled Kuna Molas: Sewn Stories and the Interplay of Tradition and Change, August 18, 2014-July 31, 2015.
Carved wood.
From the 20th century.
Keywords: Molas -- Panama; Staffs (Sticks, canes, etc.) -- Panama